Responses Contribute to Context Effects on Ratio-Setting Timing Tasks. (May 2013) - Ryan, Lawrence J; Havens, Anthony
Short durations in a range of standard durations are typically overreproduced and long durations underreproduced ('Vierordt's Law'). This contextual distortion may result from each trial assimilating the central tendency of the preceding series. We examine whether responses as well as standard durations contribute to this distortion. Two experiments using nonequal-setting ratio tasks are described. On equal-setting ratio tasks the means of the standards and responses are nearly equal, but in half-setting and double-setting standards and responses differ. In both experiments a central tendency of standards plus responses better predicted the indifference interval than did the mean of the standards alone. The coefficients of variation were larger for all double-setting conditions than for half-setting at the same response durations, suggesting pooling of the trial variance with the central tendency's variance. Longer equal-setting reproductions were generated by randomly intermixing equal-setting with double-setting than by intermixing with half-setting. Thus, assimilation of a central tendency that includes both standards and responses can account for the location of the indifference intervals ('Vierordt's Law'), for the response variation and for the additive effect we observed where two entire response curves (for equal-setting) were shifted relative to each other by the influence of nonequal-setting trials.